La influencia de padres y docentes en el desarrollo del aprendizaje inteligente, de los niños y niñas de quinto grado del subnivel de básica media, de la escuela de educación básica Benigno Bayancela del barrio San Cayetano Bajo, de la parroquia El Valle de la ciudad de Loja, período académico 2012-2013 - Yanangomez Montaño, Yolanda Lucero (2014)
The present investigation turns on: the influence of educational parents and in the development of the intelligent learning, of the children and children of fifth degree of Average Subnivel de Básica, of the Basic school of Education “Benign Bayancela” of the district San low Cayetano, of the Parish the Valley of the city of Loja, academic period 2012-2013, as opposed to which the following objectives consider: General: To characterize the influence that has the educational parents and in the development of the intelligent learning of the children and children. The methods used for the development of the present investigation were: inductive, deductive, analytical and synthetic scientist, such who helped me to the organization, processing and analysis of the information. In order to reach the data the techniques of the survey, the same one were handled that was applied educational, students and parents of family of the institution. In order to reach the results it was investigated to 3 educational ones, 39 students and 23 parents of family of the Basic school of Education “Benign Bayancela”. Coming to the conclusion that the aforementioned school students like to participate in classes in all activities posed by the teacher, teachers motivate students using the analytical method and study skills familiar content of each class, promoting the participation of students, since at the time performing readings of the different themesask the students that they underline the most important topic, likewise when they have to evaluate they anticipate two days prior to the date of assessment, in this way achieve that students respond with effectiveness evaluation questionnaires, thus obtaining a significant learning. Representatives of students appear to be very responsible with their children, they support them in their activities, bringing them the self-esteem to a very high standard, also teaches you to plan your time to carry out the activities and tasks of the school, by such habits of study that students must manage to have an intelligent learning.